2012
DOI: 10.1063/1.4739765
|View full text |Cite
|
Sign up to set email alerts
|

Revisited global drift fluid model for linear devices

Abstract: The problem of energy conserving global drift fluid simulations is revisited. It is found that for the case of cylindrical plasmas in a homogenous magnetic field, a straightforward reformulation is possible avoiding simplifications leading to energetic inconsistencies. The particular new feature is the rigorous treatment of the polarisation drift by a generalization of the vorticity equation. The resulting set of model equations contains previous formulations as limiting cases and is suitable for efficient num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…15. The equations of continuity, parallel momentum, and electron temperature describing the global profiles temporal evolution of particle density n, parallel electron velocity v jj , parallel ion velocity u jj , and electron temperature T e read @n @t…”
Section: Three-dimensional Global Drift Fluid Dynamics In Cylindrmentioning
confidence: 99%
See 2 more Smart Citations
“…15. The equations of continuity, parallel momentum, and electron temperature describing the global profiles temporal evolution of particle density n, parallel electron velocity v jj , parallel ion velocity u jj , and electron temperature T e read @n @t…”
Section: Three-dimensional Global Drift Fluid Dynamics In Cylindrmentioning
confidence: 99%
“…4,5 The numerical approach is based on an electrostatic drift fluid model for electrons and ions in a cylindrical geometry with ions assumed to be cold, T i ( T e , and electromagnetic effects assumed to be negligible, b ( 1. Drift fluid models and variants thereof (sometimes denoted as drift-reduced Braginskii models, reduced MHD models, or resistive drift wave models) are widely used for theoretical studies of plasmas in linear devices [6][7][8][9][10][11][12][13][14][15][16] and have been proven successful in the analysis and interpretation of experimental findings on statistical properties, plasma structures, instability drive, and the sensitivity of plasma dynamics on plasma sources, device dimensions, ion-neutral collisions. The particular approaches differ, e.g., in their dimensionality (2D or 3D in space), their use of scale separation (local or global approach), the treatment of axial boundary conditions (sheath conditions or periodic boundary conditions), the inclusion of non-linear dynamics (linear or non-linear models), the inclusion of electron temperature evolution (constant temperature or timedependent profiles), and the details of plasma sources (uniform in axial direction or localized).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an ambitious undertaking, as it requires the combination of neutral gas and atomic physics, plasma-wall interaction, turbulent transport, and neoclassical effects [11]. As a first step towards this, we present in section 2 a drift-reduced model [12,13,14,15] which has been constructed based on the derivation of Simakov and Catto [16], and similar to that derived in [17] but with several modifications to make it more suitable for numerical solution in global geometry. This model has good conservation properties, described in section 2.1, and has been implemented using the BOUT++ framework [18,19] using conservative numerical methods described in section 3.…”
Section: Introductionmentioning
confidence: 99%
“…In the linear plasma device NAGDIS-II (NAGoya DIvertor plasma Simulator II), fast framing camera observations have revealed that a spiral structure ejected from the plasma column was rotated in E × B direction in the peripheral region of the plasma column, where the electric field was in the radial direction [4,10]. Recent three dimensional simulation aiming at linear plasma devices predicted that resistive drift instability leads to generation of blob-like structures [11]. From the simulation, it was also suggested that the instability with m = 0 mode in the core region of the cylindrical plasma was important for the spiral structure formation in linear devices in addition to the instability with m = 1 author's e-mail: kajita.shin@nagoya-u.jp mode [12].…”
Section: Introductionmentioning
confidence: 99%